Analisis Hukum Islam terhadap Penerapan Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal di RPH Ciroyom Kota Bandung - Ilham Nur Rohman; Zaini Abdul Malik; Ira Siti Rohmah Maulida (Bandung Conference Series: Sharia Economic Law, 2026)
Abstract. The objective of this research is to analyze the implementation of Law Number 33 of 2014 concerning Halal Product Guarantee (JPH Law) at the Ciroyom Slaughterhouse (RPH) in Bandung City, as well as to review it from an Islamic legal perspective. The primary objective of the present study is to examine the implementation of regulations following the enactment of the Job Creation Law, with a focus on the refinement of halal certification governance. This includes an analysis of the registration system, the separation of facilities, and the role of related institutions. The approach employed is descriptive qualitative, with the methods comprising field observation, interviews, and legal document review. The results demonstrated that the Ciroyom abattoir has consistently met the requirements of halal certification, including the separation of halal and non-halal zones and the involvement of certified slaughterhands (JULEHA). Despite the discrepancies in duration and administrative procedures between the JPH Law prior to and following the enactment of the Job Creation Law, RPH Ciroyom has demonstrated a remarkable capacity for adjustment. A review of Islamic law reveals that the practices employed in the abattoir are consistent with the principles of thaharah, halal, and saddu al-dzari'ah. This research recommends the strengthening of synergies between institutions and continuing education for slaughterhouse industry players in order to maintain halal products as a whole and on an ongoing basis. Abstrak. Penelitian ini bertujuan untuk menganalisis penerapan Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal (UU JPH) di Rumah Potong Hewan (RPH) Ciroyom Kota Bandung, serta meninjaunya dari perspektif hukum Islam. Fokus utama penelitian mencakup implementasi regulasi setelah berlakunya Undang-Undang Cipta Kerja sebagai penyempurna tata kelola sertifikasi halal, termasuk sistem pendaftaran, pemisahan fasilitas, dan peran lembaga terkait. Pendekatan yang digunakan adalah kualitatif deskriptif dengan metode observasi lapangan, wawancara, serta telaah dokumen hukum. Hasil penelitian menunjukkan bahwa RPH Ciroyom telah memenuhi persyaratan sertifikasi halal secara konsisten, termasuk pemisahan zona halal dan non-halal serta pelibatan juru sembelih bersertifikat (JULEHA). Meskipun terjadi perbedaan dalam durasi dan prosedur administratif antara UU JPH sebelum dan sesudah UU Cipta Kerja, RPH Ciroyom tetap dapat menyesuaikan diri dengan baik. Dari tinjauan hukum Islam, praktik yang diterapkan di RPH telah sesuai dengan prinsip thaharah, kehalalan, dan saddu al-dzari'ah. Penelitian ini merekomendasikan penguatan sinergi antar lembaga serta edukasi berkelanjutan bagi pelaku industri RPH dalam menjaga kehalalan produk secara menyeluruh dan berkelanjutan.